Community Based Tourism and Strengthening of Ecopreneurship for the Development of Ecotourism in Jember - SETYANTI, Sri Wahyu Lelly Hana; YULISETIARINI, Diah; PARAMU, Hadi (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021, 2021)
Tourism is one of Indonesia's attractions and provides a very large contribution to state revenue. Jember Regency has the potential for ecotourism ocean tourism with 7 beautiful beaches ready to be developed. The purpose of this study is to explain how the concept of sustainable tourism through a Community-Based Tourism approach and how to strengthening ecopreneurship to support sustainable ecotourism. Quantitative research methods provide results that community based tourism and ecopreneurship are able to encourage an increase in sustainable ecotourism by prioritizing the potential for ocean tourism and encouraging community capacity development.